Die Baugeschichte des Freiburger Münsterturms - Koch, Nikolaus (KIT Scientific Publishing, 2023)
The Freiburg Minster spire viewed from the perspective of archaeological building research. Individual building phases of the tower are presented by means of collecting and analysing thousands of stonemason's marks appearing on the tower in multiple perspective illustrations. The three-dimensional reconstruction of the design drawing of a more than 700-year-old vellum plan vividly demonstrates that many ideas of the complex Gothic tower construction were already present in the planning.